Perubahan Iklim Terhadap Kesesuaian Lahan Agroklimat Tanaman Padi dengan Skenario SSP245, SSP370, dan SSP585 Studi Kasus Jawa Tengah - Pujiati Pujiati; Mochamad Aryono Adhi; Trinah Wati; Andreas Kristiawan; Firmansyah Firmansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the long-term impact of climate change on the agricultural sector and land suitability in Central Java—Indonesia’s third-largest rice producer. To project future atmospheric, oceanic, and land dynamics, the research utilizes the Global Climate Model (GCM) under the CMIP6 (Coupled Model Intercomparison Project Phase 6) framework. These models integrate socioeconomic factors through three specific Shared Socioeconomic Pathways: SSP2-4.5, SSP3-7.0, and SSP5-8.5, downscaled to a 25 km resolution. The analysis utilizes historical rainfall and temperature data (1991–2014) as a baseline to evaluate two future windows: the near-future (2027–2050) and the far-future (2077–2100). Employing linear regression and agro-climatic land suitability calculations for rice, the results indicate that while climate change impacts remain relatively stable in the near-term, there is a significant risk for the far-future. Specifically, agro-climatic land suitability is projected to decline in the far-future period, driven primarily by a consistent rise in average annual temperatures across Central Java. These findings serve as a critical evidence-based recommendation for regional agricultural planning and adaptation strategies. Keywords: Central Java, Agroclimate Land Suitability, Climate Change, Shared Socioeconomic Pathways